Pengaruh Kepemimpinan Lurah terhadap Kesadaran Masyarakat dalam Membayar Pajak Bumi dan Bangunan di Kelurahan Karunrung - Nur Wahid; Nurhalizah Nurhalizah; Hafiz Elfiansya Parawu (Fakultas Ilmu Sosial dan Ilmu Politik, 2019)
This study purposed to describe and explain the influence of Headman leadership on community awareness in paying Land and Building Tax (PBB) in Karunrung Village, Rappocini District, Makassar City. The type of research in this study was quantitative research. Quantitative research is a measured method with the intention to test a predetermined hypothesis. Variables were measured with research data so that the data was collected, tabulated and provides the information needed. The results showed a significant influence of village head's leadership on community awareness of paying Land and Building Tax in Karunrung Village, Rappocini District, Makassar City. The community's awareness was strongly influenced by factors; leadership, motivation and public knowledge about the urgency of taxes for regional development.